The Euclidean division of the canon: Greek and Latin Sources - Barbera, André (Lincoln University of Nebraska Press, 1991)
The Division of the Canon is an ancient Pythagorean treatise on the relationship between mathematical and acoustical truths. Euclidean in style, sectional in nature, and essentially Pythagorean, the Division has been susceptible to quotation since antiquity and has attracted the attention of many musicologists, classicists, mathematicians, and historians of science.